Pengaruh Kebijakan Moneter Terhadap Ketimpangan Pendapatan di Indonesia - Amanda Dwi Lestari; Greyuni Grace Tambunan; Raden Fadhilla Salsabila; Avrahersatiadi Ricco Galang Erlangga; Maunisa Widya Zalianty; Nurlela; Disya Ayu Rivtryana (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Monetary policy is a policy that can influence the Indonesian economy. Interest rates are one of the instruments in monetary policy. This research aims to determine the effect of interest rates on income inequality in Indonesia. The data used is secondary time series data for the period 2014 – 2023 obtained from BPS and BI using the simple linear regression method. This research shows that monetary policy on interest rates has an insignificant effect on income inequality in Indonesia. The interest rate only influences income inequality by 35% and 65% is influenced by other factors that were not studied.